Predictive technology modeling for deep-submicron MOSFET design - Wang, Yuwen. (2008)
The predictive technology modeling using numerical and compact model for deep-submicron MOSFET is explored in this thesis. The devices are designed for a broad range of nMOSFETs with different pile-up/different LDD extension under gate structures. The investigations inludes numerical modeling for threshold voltage, with different pile-up structure MOSFETs.